The Effects of Compulsory Schooling on Health and Hospitalization over the Life Cycle - Markus Gehrsitz; Jr. Williams (Institute of Labor Economics (IZA), 2024)
This paper examines the effects of education on health and hospitalization over the life cycle. Using administrative data, we leverage a 1972 compulsory schooling reform within the United Kingdom which produced a large increase in educational attainment among affected cohorts. Our regression discontinuity design estimates suggest that the reform led to substantial reductions in hospitalization among men admitted for lifestyle-related conditions. We also report novel estimates showing that these effects vary heterogeneously over the life-cycle – with the largest health improvements occurring among men in their middle-aged years. However, we find no evidence that the reform impacted mortality during working-age years.
Keywords: I10; I12; I14; I20; 330; health; education; compulsory schooling; life cycle; gender differences